Sodium alginate-based polyacrylamide hydrogel and preparation method thereof
By adding modified montmorillonite and nanotitanium dioxide to the sodium alginate-based polyacrylamide hydrogel, a tight crosslinking network and enhanced interface effect was formed, the problems of poor mechanical properties and poor heat resistance of the gel were solved, and its tensile strength and thermal stability were significantly improved.
Patent Information
- Application Number
- CN202411776431.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
AI Technical Summary
The composite gel of sodium alginate and acrylamide has poor mechanical properties and poor heat resistance, which makes it difficult to withstand large external forces, and is easily damaged in high temperature environments, affecting its stability.
By adding modified montmorillonite and nanotitanium dioxide, a tighter cross-linking network and enhanced interface effect are formed to improve the tensile strength and thermal stability of the gel. The sheet structure of modified montmorillonite hinders heat transfer, and nanotitanium dioxide has good light stability and thermal stability, further enhancing the overall structure of the gel.
It significantly improves the tensile strength and thermal stability of sodium alginate-based polyacrylamide hydrogel, solves the problems of poor mechanical properties and poor heat resistance, and enhances the stability and application range of the gel.
Smart Images

Figure CN119638894A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer chemical polymerization, and in particular to a sodium alginate-based polyacrylamide hydrogel and a preparation method thereof. Background Art
[0002] There are a large number of hydroxyl and carboxyl groups in the sodium alginate chain segment, which has the advantages of good biocompatibility, low toxicity and biodegradability of natural polysaccharides. The reaction conditions are mild and it can combine with divalent metal ions through physical interaction to form a tighter cross-linked structure. It can also form a high-density network structure by chemical cross-linking. Good achievements have been made in the fields of drug carriers, wound dressings, medical hydrogels, etc.
[0003] However, sodium alginate hydrogel still has many defects, such as poor adsorption performance, simple drug loading method, easy burst release during drug release and short drug sustained release time, low mechanical strength and poor stability. In the related art, sodium alginate and acrylamide are compounded to prepare gel. Although sodium alginate and acrylamide can form a cross-linked network, their tensile strength at break is relatively low, making it difficult to withstand large external forces, and their toughness is poor. When subjected to a large degree of stretching or deformation, they are prone to rupture or breakage. In some environments that require higher temperatures, the structure and properties of the gel will change significantly, and the change is usually irreversible. It is easily damaged at high temperatures, affecting the stability of the gel. Summary of the invention
[0004] The present application provides a sodium alginate-based polyacrylamide hydrogel and a preparation method thereof, so as to solve the problems of poor mechanical properties and poor heat resistance of the sodium alginate and acrylamide composite gel in the related art.
[0005] In a first aspect, a sodium alginate-based polyacrylamide hydrogel is provided, which comprises, by weight:
[0006] 10-20 parts of acrylamide, 10-15 parts of sodium alginate, 3-7 parts of modified montmorillonite, 1-3 parts of nano titanium dioxide, 0.3-0.9 parts of anhydrous calcium chloride, 0.1-0.5 parts of a cross-linking agent, a photoinitiator and tetramethylethylenediamine, wherein the mass fraction of the photoinitiator is 0.5-2% of the mass fraction of acrylamide, and the mass fraction of the tetramethylethylenediamine is 1-3 times that of the photoinitiator;
[0007] The preparation of the modified montmorillonite comprises the following steps:
[0008] a. Disperse montmorillonite in deionized water at a mass volume ratio of 1:20 to 1:50, stir evenly at a speed of 300 to 500 r / min, add hexadecyltrimethylammonium bromide, continue stirring at a speed of 500 to 800 r / min for 10 to 30 minutes, and then stir and react at a speed of 200 to 300 r / min for 2 to 4 hours. The mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:3 to 1:5;
[0009] b. Centrifuge the product obtained in step a at a speed of 3000 to 5000 r / min for 5 to 10 min.
[0010] Preferably, the cross-linking agent is selected from one of N,N-methylenebisacrylamide and genipin.
[0011] Preferably, the photoinitiator is selected from one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4-diethylthioxanthone.
[0012] Preferably, it further comprises urea, and the mass of the urea accounts for 3% of the mass of the acrylamide.
[0013] In a second aspect, a method for preparing a sodium alginate-based polyacrylamide hydrogel is provided, which is used to prepare any of the sodium alginate-based polyacrylamide hydrogels described above, and is characterized in that it comprises the following steps:
[0014] S1. preparing modified montmorillonite;
[0015] S2. Prepare a sodium alginate-modified montmorillonite solution: dissolve 10 to 15 parts of sodium alginate in 500 parts of deionized water by weight and mix and stir to obtain a sodium alginate solution at a stirring speed of 300 to 500 r / min;
[0016] After adding 3 to 7 parts of modified montmorillonite to the sodium alginate solution, continue mixing and stirring at a speed of 300 to 500 r / min for 30 to 60 minutes to obtain a sodium alginate-modified montmorillonite solution;
[0017] S3, preparing acrylamide solution;
[0018] S4, forming an ion cross-linked network: adding a 0.2 mol / L calcium chloride solution to the sodium alginate-modified montmorillonite solution at a stirring speed of 100 to 200 r / min to obtain an intermediate product, wherein the mass fraction of the calcium chloride is 0.4 to 0.9 parts;
[0019] The intermediate product is immersed in a cross-linking agent solution and allowed to stand for 6 to 24 hours to undergo a cross-linking reaction to obtain a primary product, wherein the cross-linking agent is selected from one of N,N-methylenebisacrylamide and genipin;
[0020] S5, preparing a nano titanium dioxide dispersion: dispersing 1 to 3 parts of nano titanium dioxide in 50 parts of deionized water and ultrasonically treating for 30 to 60 minutes to obtain a nano titanium dioxide dispersion;
[0021] S6, photoinitiated polymerization: slowly add the acrylamide solution and the nano-titanium dioxide dispersion to the primary product, and irradiate under 365nm ultraviolet light for 10 to 30 minutes to obtain a hydrogel, wherein the mass volume ratio of the primary product to the acrylamide solution is 1:1 to 1:3, and the mass volume ratio of the primary product to the nano-titanium dioxide dispersion is 1:5 to 1:10.
[0022] Preferably, S3 includes:
[0023] After 10 to 20 parts of acrylamide and deionized water are mixed in a mass ratio of 1:5 to 1:10, a photoinitiator and tetramethylethylenediamine are added, and the mixture is stirred at a speed of 300 to 500 r / min for 15 to 30 minutes to obtain an acrylamide solution, wherein the amount of the photoinitiator added is 0.5 to 2% of the mass of the acrylamide, and the amount of the tetramethylethylenediamine added is 1 to 3 times the mass of the photoinitiator.
[0024] Preferably, after S5, the step further includes post-processing the gel:
[0025] The gel was immersed in deionized water, and the deionized water was replaced every 30 minutes. After the deionized water was replaced 5 times, the post-treatment of the gel was completed.
[0026] Preferably, the particle size of the nano titanium dioxide is 5 to 30 nm.
[0027] Preferably, in S5, the ultrasonic power is 200-400W.
[0028] The beneficial effects of the technical solution provided by this application include:
[0029] The present application provides a sodium alginate-based polyacrylamide hydrogel and a preparation method thereof, wherein montmorillonite is added. The montmorillonite itself has a lamellar structure and participates in the construction of a gel network as a physical crosslinking point. After being modified with hexadecyltrimethylammonium bromide, the lamellar structure hinders the transfer of heat and excessive thermal motion of molecular chains, so that the hydrogel can maintain stable performance within a relatively high temperature range; at the same time, the modified montmorillonite has better dispersibility, and its surface functional map and the quaternary ammonium salt head of hexadecyltrimethylammonium bromide produce ion exchange with negatively charged groups such as carboxyl groups of sodium alginate, thereby enhancing the interface effect and thus improving the tensile strength of the hydrogel;
[0030] Nano-titanium dioxide itself has good photostability and certain photocatalytic properties. As a stable inorganic filler in the hydrogel, it plays a role in blocking heat transfer and absorbing and dispersing excess energy to a certain extent, further improving the thermal stability of the hydrogel. Therefore, it can solve the problems of poor mechanical properties and poor heat resistance of the composite gel of sodium alginate and acrylamide in related technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 A flow chart for the preparation of sodium alginate-based polyacrylamide hydrogel provided in this application;
[0033] Figure 2 Schematic diagram of TG and DTG curves of the hydrogel obtained in Example 3 provided in this application;
[0034] Figure 3 This is a schematic diagram of the TG and DTG curves of the hydrogel obtained in Comparative Example 2 provided in the present application. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0036] The present application provides a method for preparing a sodium alginate-based polyacrylamide hydrogel, which can solve the problems of poor mechanical properties and poor heat resistance of the sodium alginate and acrylamide composite gel in the related art.
[0037] See also Figures 1 to 3 As shown, the present application provides a sodium alginate-based polyacrylamide hydrogel, and the preparation method thereof comprises the following steps:
[0038] S1. Preparation of modified montmorillonite:
[0039] a. Disperse montmorillonite in deionized water at a mass volume ratio of 1:20 to 1:50, stir evenly at a speed of 300 to 500 r / min, add hexadecyltrimethylammonium bromide, continue stirring at a speed of 500 to 800 r / min for 10 to 30 minutes, and then stir and react at a speed of 200 to 300 r / min for 2 to 4 hours. The mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:3 to 1:5;
[0040] b. The product obtained in step a is centrifuged at a speed of 3000 to 5000 rpm for 5 to 10 min.
[0041] Specifically, montmorillonite is stirred in water at high speed, using mechanical force to overcome the agglomeration force between its flakes, so that it is evenly dispersed in water to form a dispersion, so that it can be better mixed with other raw materials and evenly distributed in the hydrogel system.
[0042] S2. Prepare a sodium alginate-modified montmorillonite solution: dissolve 10 to 15 parts of sodium alginate in 500 parts of deionized water by weight and mix and stir to obtain a sodium alginate solution at a stirring speed of 300 to 500 r / min;
[0043] After adding 3 to 7 parts of modified montmorillonite to the sodium alginate solution, continue mixing and stirring at a speed of 300 to 500 r / min for 30 to 60 minutes to obtain a sodium alginate-modified montmorillonite solution;
[0044] S3, preparing acrylamide solution:
[0045] After 10 to 20 parts of acrylamide and deionized water are mixed in a mass ratio of 1:5 to 1:10, a photoinitiator and tetramethylethylenediamine are added, and the mixture is stirred at a speed of 300 to 500 r / min for 15 to 30 minutes to obtain an acrylamide solution, wherein the amount of the photoinitiator added is 0.5 to 2% of the mass of the acrylamide, and the amount of the tetramethylethylenediamine added is 1 to 3 times the mass of the photoinitiator.
[0046] In some embodiments, the photoinitiator is selected from one of TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide) and DETX (2,4-diethylthioxanthone).
[0047] S4, forming an ion cross-linked network: adding a 2 mol / L calcium chloride solution to the sodium alginate-modified montmorillonite solution at a stirring speed of 100 to 200 r / min to obtain an intermediate product, wherein the mass fraction of the calcium chloride is 0.4 to 0.9 parts;
[0048] The intermediate product is immersed in a crosslinking agent solution containing 0.1 to 0.5 parts of a crosslinking agent (based on immersing the intermediate product), and allowed to stand for 6 to 24 hours to perform a crosslinking reaction to obtain a primary product, wherein the crosslinking agent is selected from one of N,N-methylenebisacrylamide and genipin.
[0049] Specifically, sodium alginate and Ca 2+ The ionic electrostatic effect forms an ionic cross-linked network, and the lamellar structure of montmorillonite is interspersed in the sodium alginate network. During the ionic cross-linking process, on the one hand, montmorillonite will restrict the movement of the sodium alginate molecular chain and further enhance the mechanical properties of the gel; on the other hand, the adsorption properties of montmorillonite itself will also synergize with the ionic cross-linked network to improve the adsorption properties of the hydrogel.
[0050] S5. Prepare nano titanium dioxide dispersion: disperse 1 to 3 parts of nano titanium dioxide in 50 parts of deionized water and perform ultrasonic treatment for 30 to 60 minutes to obtain a nano titanium dioxide dispersion; after the ultrasonic treatment, the agglomeration between the nano titanium dioxide particles is broken, so that the nano titanium dioxide particles can be evenly dispersed in water.
[0051] In some embodiments, the particle size of the nano titanium dioxide is 5 to 30 nm.
[0052] In some embodiments, the ultrasonic power is 200-400W.
[0053] S6, photoinitiated polymerization: slowly add the acrylamide solution and the nano-titanium dioxide dispersion to the primary product, and irradiate under 365nm ultraviolet light for 10 to 30 minutes to obtain a hydrogel, wherein the mass volume ratio of the primary product to the acrylamide solution is 1:1 to 1:3, and the mass volume ratio of the primary product to the nano-titanium dioxide dispersion is 1:5 to 1:10.
[0054] Specifically, nano-titanium dioxide has good stability and photocatalytic activity. It is evenly dispersed in the hydrogel network, and enhances the overall structure of the hydrogel and improves the mechanical properties through interaction with polymer chains. At the same time, the thermal stability of nano-titanium dioxide also helps to improve the thermal stability of the hydrogel.
[0055] Example 1
[0056] The preparation method of sodium alginate-based polyacrylamide hydrogel provided in this embodiment comprises the following steps:
[0057] S1. Preparation of modified montmorillonite:
[0058] a. Disperse 10 g of montmorillonite in 200 mL of deionized water, stir evenly at 300 r / min using a magnetic stirrer, add 2 g of hexadecyltrimethylammonium bromide, increase the stirring speed to 500 r / min, and continue stirring for 30 min to completely dissolve the hexadecyltrimethylammonium bromide (CTAB) and mix evenly with the montmorillonite, reduce the stirring speed to 300 r / min, react for 2 h, and perform organic modification;
[0059] b. Centrifuge the product obtained in step a to obtain modified montmorillonite at a centrifugal speed of 3000 r / min and a centrifugal time of 10 min.
[0060] S2. Preparation of sodium alginate-modified montmorillonite solution:
[0061] 10 g of sodium alginate and 500 mL of deionized water were mixed and stirred at a speed of 300 r / min to obtain a sodium alginate solution;
[0062] After adding 3 g of modified montmorillonite to the sodium alginate solution, the mixture was stirred at a speed of 300 r / min for 60 min to obtain a sodium alginate-modified montmorillonite solution.
[0063] S3, preparing acrylamide solution:
[0064] After mixing 10 g of acrylamide with 100 mL of deionized water, 0.05 g of TPO and 0.05 g of tetramethylethylenediamine were added, and the mixture was stirred at a speed of 300 r / min for 30 min to obtain an acrylamide solution.
[0065] S4, forming an ion cross-linked network: adding 20 mL of 0.2 mol / L calcium chloride solution to the sodium alginate-modified montmorillonite solution obtained in S2 at a stirring speed of 100 r / min to obtain an intermediate product;
[0066] 0.1 g of N,N-methylenebisacrylamide was dissolved in 100 mL of deionized water to obtain an N,N-methylenebisacrylamide solution. The intermediate product was immersed in the N,N-methylenebisacrylamide solution and allowed to stand for 6 hours to perform a cross-linking reaction to obtain a primary product.
[0067] S5. Preparation of nano titanium dioxide dispersion:
[0068] 1 g of nano titanium dioxide with a particle size range of 5 to 10 nm was mixed with 50 mL of deionized water and ultrasonically treated for 30 min to obtain a nano titanium dioxide dispersion, wherein the ultrasonic power was 200 W.
[0069] S6, photo-initiated polymerization: slowly add the acrylamide solution prepared in S3 and the nano-titanium dioxide dispersion prepared in S5 to the primary product prepared in S4, and irradiate under 365 nm ultraviolet light for 10 minutes to obtain a hydrogel.
[0070] Example 2
[0071] The preparation method of sodium alginate-based polyacrylamide hydrogel provided in this embodiment comprises the following steps:
[0072] S1. Preparation of modified montmorillonite:
[0073] a. Disperse 9 g of montmorillonite in 450 mL of deionized water, stir evenly at 500 r / min using a magnetic stirrer, add 3 g of hexadecyltrimethylammonium bromide, increase the stirring speed to 800 r / min, and continue stirring for 10 min to completely dissolve the hexadecyltrimethylammonium bromide (CTAB) and mix evenly with the montmorillonite, reduce the stirring speed to 200 r / min, react for 4 h, and perform organic modification;
[0074] b. Centrifuge the product obtained in step a to obtain modified montmorillonite at a centrifugal speed of 5000 r / min and a centrifugal time of 5 min.
[0075] S2. Preparation of sodium alginate-modified montmorillonite solution:
[0076] 15 g of sodium alginate and 500 mL of deionized water were mixed and stirred at a speed of 500 r / min to obtain a sodium alginate solution;
[0077] After adding 7 g of modified montmorillonite to the sodium alginate solution, the mixture was stirred at a speed of 500 r / min for 30 min to obtain a sodium alginate-modified montmorillonite solution.
[0078] S3, preparing acrylamide solution:
[0079] After mixing 20 g of acrylamide with 200 mL of deionized water, 0.2 g of TPO and 0.05 g of tetramethylethylenediamine were added, and the mixture was stirred at a speed of 500 r / min for 15 min to obtain an acrylamide solution.
[0080] S4, forming an ion cross-linked network: adding 30 mL of 0.3 mol / L calcium chloride solution to the sodium alginate-modified montmorillonite solution obtained in S2 at a stirring speed of 200 r / min to obtain an intermediate product;
[0081] 0.5 g of N,N-methylenebisacrylamide was dissolved in 100 mL of deionized water to obtain an N,N-methylenebisacrylamide solution. The intermediate product was immersed in the N,N-methylenebisacrylamide solution and allowed to stand for 12 hours to perform a cross-linking reaction to obtain a primary product.
[0082] S5. Preparation of nano titanium dioxide dispersion:
[0083] 3 g of nano titanium dioxide with a particle size range of 20 to 30 nm was mixed with 50 mL of deionized water and ultrasonically treated for 60 min to obtain a nano titanium dioxide dispersion, wherein the ultrasonic power was 400 W.
[0084] S6, photo-initiated polymerization: slowly add the acrylamide solution prepared in S3 and the nano-titanium dioxide dispersion prepared in S5 to the primary product prepared in S4, and irradiate under 365 nm ultraviolet light for 30 minutes to obtain a hydrogel.
[0085] Example 3
[0086] The preparation method of sodium alginate-based polyacrylamide hydrogel provided in this embodiment comprises the following steps:
[0087] S1. Preparation of modified montmorillonite:
[0088] a. Disperse 10 g of montmorillonite in 300 mL of deionized water, stir evenly at 400 r / min using a magnetic stirrer, add 2.5 g of hexadecyltrimethylammonium bromide, increase the stirring speed to 600 r / min, and continue stirring for 20 min to completely dissolve the hexadecyltrimethylammonium bromide (CTAB) and mix evenly with the montmorillonite, reduce the stirring speed to 250 r / min, react for 3 h, and carry out organic modification;
[0089] b. Centrifuge the product obtained in step a to obtain modified montmorillonite at a centrifugal speed of 3500 r / min and a centrifugal time of 6 min.
[0090] S2. Preparation of sodium alginate-modified montmorillonite solution:
[0091] 12 g of sodium alginate and 500 mL of deionized water were mixed and stirred at a speed of 400 r / min to obtain a sodium alginate solution;
[0092] After adding 5 g of modified montmorillonite to the sodium alginate solution, the mixture was stirred at a speed of 400 r / min for 45 min to obtain a sodium alginate-modified montmorillonite solution.
[0093] S3, preparing acrylamide solution:
[0094] After mixing 15 g of acrylamide with 100 mL of deionized water, 0.3 g of DETX and 0.6 g of tetramethylethylenediamine were added, and the mixture was stirred at a speed of 400 r / min for 20 min to obtain an acrylamide solution.
[0095] S4, forming an ion cross-linked network: adding 50 mL of 0.1 mol / L calcium chloride solution to the sodium alginate-modified montmorillonite solution obtained in S2 at a stirring speed of 150 r / min to obtain an intermediate product;
[0096] 0.3 g of genipin was dissolved in 100 mL of deionized water to obtain a genipin solution. The intermediate product was immersed in the genipin solution and allowed to stand for 24 hours to perform a cross-linking reaction to obtain a primary product.
[0097] S5. Preparation of nano titanium dioxide dispersion:
[0098] 2 g of nano titanium dioxide with a particle size range of 10 to 20 nm was mixed with 50 mL of deionized water and ultrasonically treated for 45 min to obtain a nano titanium dioxide dispersion, wherein the ultrasonic power was 300 W.
[0099] S6, photo-initiated polymerization: slowly adding the acrylamide solution prepared in S3 and the nano-titanium dioxide dispersion prepared in S5 to the primary product prepared in S4, and irradiating under 365 nm ultraviolet light for 20 minutes to obtain a hydrogel;
[0100] The hydrogel was immersed in deionized water, and the deionized water was replaced every 30 minutes. After the deionized water was replaced 5 times, the post-treatment of the hydrogel was completed.
[0101] Example 4
[0102] The preparation method of sodium alginate-based polyacrylamide hydrogel provided in this embodiment comprises the following steps:
[0103] S1. Preparation of modified montmorillonite:
[0104] a. Disperse 10 g of montmorillonite in 400 mL of deionized water, stir evenly at 400 r / min using a magnetic stirrer, add 2.5 g of hexadecyltrimethylammonium bromide, increase the stirring speed to 600 r / min, and continue stirring for 20 min to completely dissolve the hexadecyltrimethylammonium bromide (CTAB) and mix evenly with the montmorillonite, reduce the stirring speed to 250 r / min, react for 2 h, and perform organic modification;
[0105] b. Centrifuge the product obtained in step a to obtain modified montmorillonite at a centrifugal speed of 3000 r / min and a centrifugal time of 10 min.
[0106] S2. Preparation of sodium alginate-modified montmorillonite solution:
[0107] 13 g of sodium alginate and 500 mL of deionized water were mixed and stirred at a speed of 400 r / min to obtain a sodium alginate solution;
[0108] After adding 6 g of modified montmorillonite to the sodium alginate solution, the mixture was stirred at a speed of 400 r / min for 45 min to obtain a sodium alginate-modified montmorillonite solution.
[0109] S3, preparing acrylamide solution:
[0110] After mixing 12 g of acrylamide with 100 mL of deionized water, 0.36 g of urea, 0.18 g of DETX and 0.54 g of tetramethylethylenediamine were added, and the mixture was stirred at a speed of 400 r / min for 20 min to obtain an acrylamide solution.
[0111] S4, forming an ion cross-linked network: adding 25 mL of 0.3 mol / L calcium chloride solution to the sodium alginate-modified montmorillonite solution obtained in S2 at a stirring speed of 100 r / min to obtain an intermediate product;
[0112] 0.4 g of N,N-methylenebisacrylamide was dissolved in 100 mL of deionized water to obtain an N,N-methylenebisacrylamide solution. The intermediate product was immersed in the N,N-methylenebisacrylamide solution and allowed to stand for 20 hours to perform a cross-linking reaction to obtain a primary product.
[0113] S5. Preparation of nano titanium dioxide dispersion:
[0114] 2.5 g of nano titanium dioxide with a particle size range of 5 to 15 nm was mixed with 50 mL of deionized water and ultrasonically treated for 45 min to obtain a nano titanium dioxide dispersion, wherein the ultrasonic power was 250 W.
[0115] S6, photo-initiated polymerization: slowly adding the acrylamide solution prepared in S3 and the nano-titanium dioxide dispersion prepared in S5 to the primary product prepared in S4, and irradiating under 365 nm ultraviolet light for 20 minutes to obtain a hydrogel;
[0116] The hydrogel was immersed in deionized water, and the deionized water was replaced every 30 minutes. After the deionized water was replaced 5 times, the post-treatment of the hydrogel was completed.
[0117] Example 5
[0118] The difference between this embodiment and embodiment 3 is that the amount of modified montmorillonite added in S2 is 7 g.
[0119] Comparative Example 1
[0120] The difference between this comparative example and Example 3 is that the modification operation of S1 is not performed, and the washed montmorillonite is directly added to S2.
[0121] Comparative Example 2
[0122] The difference between this comparative example and Example 3 is that S1 is not performed and montmorillonite or modified montmorillonite is not added to S2.
[0123] Comparative Example 3
[0124] The difference between this comparative example and Example 3 is that S5 is not performed and nano-titanium dioxide dispersion is not added in S6.
[0125] The hydrogels obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were dried in a vacuum oven at 70° C. and then subjected to a tensile property test. The results are shown in Table 1.
[0126] Table 1
[0127] Tensile strength(MPa) Elongation at break (%) Example 1 0.76 505 Example 2 0.71 514 Example 3 0.88 502 Example 4 0.85 510 Example 5 0.69 489 Comparative Example 1 0.32 397 Comparative Example 2 0.37 366 Comparative Example 3 0.78 472
[0128] In Example 5, more montmorillonite is added compared to Example 3, indicating that the lamellar structure of montmorillonite affects the dispersion and cross-linking environment of the system, resulting in a certain degree of decrease in the elongation at break;
[0129] By comparing Example 3 with Comparative Example 3, it can be seen that adding titanium dioxide to the hydrogel makes it have the functionality of nano titanium dioxide, so as to increase the strength and mechanical modulus of the hydrogel.
[0130] See also Figure 2 and Figure 3 As shown, Figure 2 TG and DTG curve schematic diagram of Example 3, Figure 3Schematic diagram of TG and DTG curves of Comparative Example 2. The hydrogel was tested by thermogravimetric analysis. The results showed that the initial decomposition temperature of the gel in Example 3 was 50°C higher than that in Comparative Example 2, which broadened the application scenarios in high temperature environments.
[0131] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A sodium alginate-based polyacrylamide hydrogel, characterized in that: In parts by mass, it includes: 10-20 parts of acrylamide, 10-15 parts of sodium alginate, 3-7 parts of modified montmorillonite, 1-3 parts of nano titanium dioxide, 0.3-0.9 parts of anhydrous calcium chloride, 0.1-0.5 parts of a cross-linking agent, a photoinitiator and tetramethylethylenediamine, wherein the mass fraction of the photoinitiator is 0.5-2% of the mass fraction of acrylamide, and the mass fraction of the tetramethylethylenediamine is 1-3 times that of the photoinitiator; The preparation of the modified montmorillonite comprises the following steps: a. Disperse montmorillonite in deionized water at a mass volume ratio of 1:20 to 1:50, stir evenly at a speed of 300 to 500 r / min, add hexadecyltrimethylammonium bromide, continue stirring at a speed of 500 to 800 r / min for 10 to 30 minutes, and then stir and react at a speed of 200 to 300 r / min for 2 to 4 hours. The mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:3 to 1:5; b. The product obtained in step a is centrifuged at a speed of 3000 to 5000 r / min for 5 to 10 min.
2. The sodium alginate-based polyacrylamide hydrogel according to claim 1, characterized in that: The cross-linking agent is selected from one of N,N-methylenebisacrylamide and genipin.
3. The sodium alginate-based polyacrylamide hydrogel according to claim 1, characterized in that: The photoinitiator is selected from one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4-diethylthioxanthone.
4. The sodium alginate-based polyacrylamide hydrogel according to claim 1, characterized in that: The invention also comprises urea, the mass of which accounts for 3% of the mass of the acrylamide.
5. A method for preparing a sodium alginate-based polyacrylamide hydrogel, which is used to prepare the sodium alginate-based polyacrylamide hydrogel according to any one of claims 1 to 4, characterized in that: It includes the following steps: S1. preparing modified montmorillonite; S2. Prepare a sodium alginate-modified montmorillonite solution: dissolve 10 to 15 parts of sodium alginate in 500 parts of deionized water by weight and mix and stir to obtain a sodium alginate solution at a stirring speed of 300 to 500 r / min; After adding 3 to 7 parts of modified montmorillonite to the sodium alginate solution, continue mixing and stirring at a speed of 300 to 500 r / min for 30 to 60 minutes to obtain a sodium alginate-modified montmorillonite solution; S3, preparing acrylamide solution; S4, forming an ion cross-linked network: adding a 0.2 mol / L calcium chloride solution to the sodium alginate-modified montmorillonite solution at a stirring speed of 100 to 200 r / min to obtain an intermediate product, wherein the mass fraction of the calcium chloride is 0.4 to 0.9 parts; The intermediate product is immersed in a cross-linking agent solution and allowed to stand for 6 to 24 hours to undergo a cross-linking reaction to obtain a primary product, wherein the cross-linking agent is selected from one of N,N-methylenebisacrylamide and genipin; S5, preparing a nano titanium dioxide dispersion: dispersing 1 to 3 parts of nano titanium dioxide in 50 parts of deionized water and ultrasonically treating for 30 to 60 minutes to obtain a nano titanium dioxide dispersion; S6, photoinitiated polymerization: slowly add the acrylamide solution and the nano-titanium dioxide dispersion to the primary product, and irradiate under 365nm ultraviolet light for 10 to 30 minutes to obtain a hydrogel, wherein the mass volume ratio of the primary product to the acrylamide solution is 1:1 to 1:3, and the mass volume ratio of the primary product to the nano-titanium dioxide dispersion is 1:5 to 1:
10.
6. The method for preparing sodium alginate-based polyacrylamide hydrogel according to claim 5, characterized in that: The S3 includes: After 10 to 20 parts of acrylamide and deionized water are mixed in a mass ratio of 1:5 to 1:10, a photoinitiator and tetramethylethylenediamine are added, and the mixture is stirred at a speed of 300 to 500 r / min for 15 to 30 minutes to obtain an acrylamide solution, wherein the amount of the photoinitiator added is 0.5 to 2% of the mass of the acrylamide, and the amount of the tetramethylethylenediamine added is 1 to 3 times the mass of the photoinitiator.
7. The method for preparing sodium alginate-based polyacrylamide hydrogel according to claim 5, characterized in that: After S5, the gel is post-processed as follows: The gel was immersed in deionized water, and the deionized water was replaced every 30 minutes. After the deionized water was replaced 5 times, the post-treatment of the gel was completed.
8. The method for preparing sodium alginate-based polyacrylamide hydrogel according to claim 5, characterized in that: The particle size of the nano titanium dioxide is 5 to 30 nm.
9. The method for preparing sodium alginate-based polyacrylamide hydrogel according to claim 5, characterized in that: In S5, the ultrasonic power is 200-400W.
Citation Information
Cited By
Profile control agent for shale oil reservoir and preparation method thereof
CN122444929A